Perancangan Buku Batik Tulis Jarak Arum Ex-lokalisasi Dolly Dengan Teknik Watercolor Guna Meningkatkan Brand Awareness - Faranniziah, Eka Anggi; Budiardjo, Hardman; Hidayat, Wahyu (Jurnal Art Nouveau, 2016)
Batik tulis Jarak Arum is one of the unique batik Surabaya from ex-Dolly. Jarak Arum's batik has its own characteristics which is illustrated by the motifs, where the motive is to tell about the ex-Dolly localization earlier known as the second largest in Asia. Through motives contained in batik is expected to lift the image of Dolly earlier known as localization region the second largest in Asia which has now been folded Dolly now exists in name only. With this in mind to improve the image of the previous Dolly to become one of the tourist areas in Surabaya which is famous for its batik is batik tulis Jarak Arum, is expected to change the image of Dolly the better. Batik tulis Jarak Arum also including new products that require media for recognition, in order to be able to become one of the products that can be remembered and recognized by the public. Therefore, this research aims to design book of batik tulis Jarak Arum ex-Dolly with watercolor techniques in order to increase brand awareness. The design of the book batik tulis Jarak Arum ex-Dolly using qualitative data collection methods, namely by interviews, observation, literature study, existing studies and creative brief is very important to define the concept design study. From the analysis of these data, the theme of the design concept obtained is charming. Concepts Charming aims to communicate to the target market, namely the premature adults who are less familiar and interested to be more familiar and batik and recall batik tulis Jarak Arum as part of a product category, with emphasis on product charming character. Keywords: Books Batik, Batik Distance Arum Ex-Dolly, Watercolor Techniques, Brand Awareness, Charming.